Research With Refugees and Vulnerable Populations in a Post-COVID World: Challenges and Opportunities - Saad, Bassem; George, Sophie A; Bazzi, Celine; Gorski, Kathleen; Abou-Rass, Noor; Shoukfeh, Rajaa; Javanbakht, Arash (Journal of the American Academy of Child and Adolescent Psychiatry, 2022)
At the Stress, Trauma and Anxiety Research Clinic (STARC) at Wayne State University in Detroit, we are currently amid data collection for a longitudinal prospective study of Syrian refugee children and their parents. Funded by the Eunice Kennedy Shriver National Institute of Child Health and Human Development, our goal is to understand the impact of exposure to war trauma and the stress of migration on symptoms of posttraumatic stress disorder, anxiety, and depression, as well as the neurobiological, epigenetic, and environmental correlates of risk and resilience. Like many research groups around the world, the COVID-19 pandemic brought our work to a screeching halt. Researchers who, like us, were engaged in human subjects research were left grappling with the question of how to continue their work while ensuring the safety of both research staff and participants, and while maintaining scientific integrity. In March 2020, our institution halted all in-person human subjects research that did not have direct benefits to participants, which continued until October, when research activity was resumed subject to implementation of modified procedures. Over the past 2 years, we have pivoted, adapted, and flexed, ultimately making changes that have allowed us to continue successful data collection throughout the pandemic. This article will discuss the specific challenges of working with ethnically minoritized and immigrant populations during the pandemic, the adaptations that we implemented to enable safe and effective data collection, as well as the new knowledge that we can apply to future research protocols.